2021
DOI: 10.1021/acs.macromol.0c02490
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Study of Monofunctional Vinyl Cyclopropanes Bearing Hydrogen Bond Enabling Side Chains

Abstract: The synthesis of four different monofunctional vinyl cyclopropane (VCP) derivatives and their polymerization behavior is presented. The different VCPs have different capabilities to form hydrogen bonds in their side chain. A preorganization due to these hydrogen bonds should lead to a fast polymerization. Kinetic studies, hydrogen-bond strength, and theoretical calculations were used to correlate the degree of conversion and the amount of preorganization. While VCPs capable of hydrogen bonding did not show a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Although H-bonding influenced the rate of polymerization, the difference among the different functional groups was little, as the hydrogen bonding site was too far from the active site. [13] This finding agrees with a previous report, where the rate of polymerization could be correlated to the distance between hydrogen bond and active site for acrylate monomers. [14] Therefore, we now present a new set of monomers, which bear Hbonding sites at two different positions in VCPs: an amide group linking the sidechain to the cyclopropane ring and different organic functional groups (amide, urethane, and urea) capable of H-bonding to different extents in the side chain to compare their behavior in free-radical photopolymerization concerning the rate of polymerization, and monomer conversion.…”
Section: Introductionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although H-bonding influenced the rate of polymerization, the difference among the different functional groups was little, as the hydrogen bonding site was too far from the active site. [13] This finding agrees with a previous report, where the rate of polymerization could be correlated to the distance between hydrogen bond and active site for acrylate monomers. [14] Therefore, we now present a new set of monomers, which bear Hbonding sites at two different positions in VCPs: an amide group linking the sidechain to the cyclopropane ring and different organic functional groups (amide, urethane, and urea) capable of H-bonding to different extents in the side chain to compare their behavior in free-radical photopolymerization concerning the rate of polymerization, and monomer conversion.…”
Section: Introductionsupporting
confidence: 93%
“…1 H-(300 MHz) and 13 C-nuclear magnetic resonance (NMR) spectra (75 MHz) were recorded on a Bruker Ultrashied-300 spectrometer at room temperature. To distinguish between primary and tertiary or secondary and quarterly carbons, 13 C Attached Proton Test (APT) was conducted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 4–6 , the polymerization rate of 6 was faster than those of 4 – 5 and those of 4 and 5 were the same. Recently, Agarwal et al have revealed no effect of hydrogen bonding on the polymerization rate by the comparison of VCP monomers with or without hydrogen bonding . The abovementioned results can be explained from the perspective of the influence of the steric hindrance on the acrylate moiety.…”
Section: Resultsmentioning
confidence: 98%